Resource configurations, generic strategies, and firm performance: Exploring the parallels between resource-based and competitive strategy theories in a new industry - Thomas, Howard (Institutional Knowledge at Singapore Management University, 2008)
Purpose – This paper, anchored in the resource-based view of the firm, attempts to develop linkages between firm-level resources, Porter's competitive strategy space and firm performance and explores them in the context of a new industry – the marketing technology industry. Design/methodology/approach – In the marketing technology industry the authors classify resource configurations (generalists, specialists, innovators) which group firms with distinctive competences on similar resource dimensions. They then map these firm-level resource configurations onto their respective optimal strategies in the industry's competitive strategy space. Findings – The major findings are: some firms that are close together in strategy space vary in performance; some firms that are close together in strategy space belong to quite different resource configurations; firms that belong to the same resource configuration (i.e. are close together in resource space and distant from others) vary in performance; given the origin (i.e. resource configuration) of a new entrant there exists an optimal strategy that can be theoretically defined; and corresponding to each resource configuration there seems to exist a unique optimal region in strategy space. Originality/value – It is one of few attempts to empirically explore the parallels between firm level resource-based and industry level competitive strategies.